Giant Cell Tumor of the Phalanx of Finger: Case Reports - Utomo, Pamudji; Idulhaq, Mujaddid; Mudigdo, Ambar; Sentana, Okkie Mharga (Indonesian Journal of Medicine, 2019)
Background: Giant cell tumor (GCT) of bone arising from aphalanx of finger is extremely rare. Although, the occurrence of GCT in the hands is a rare, it has been reported that GCT of the small bones (small-bone GCT) carries a higher risk of local recurrence and metastasis than conventional GCT.Subjects and Method: We report two cases of GCT arising from a phalanx of a hand finger. First patient was treated with wide excision of the tumor and fusion with fibular bone graft with the help of a K-wire. Second patient was treated by excision of tumour (Curretage) with allograft bonegraft for bone defect.Results: At their most recent follow-ups (4 months, respectively), both were recurrence free and had returned to their previous occupational and recreational activities.Conclusion: The effectiveness of these methods in the treatment and prevention of recurrence is still under discussion and there is no gold standard for treating GCT.Keywords: GCT, phalanx of finger, excision, illiac crest bonegraft, allograftCorrespondence: Pamudji Utomo. Department of Orthopaedic and Traumatology, Faculty of Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java. Email: utomodr@yahoo.com.Indonesian Journal of Medicine (2019), 4(1): 65-74https://doi.org/10.26911/theijmed.2019.04.01.11